Erratum: Idrees, M. & Zhiyong, Z. (2022) Lectotypification of 16 names in Rubus subg. Idaeobatus, 12 names in R. subg. Malachobatus, and 1 name in R. subg. Chamaebatus (Rosaceae). Phytotaxa 559 (1): 13–24. - Idrees, Muhammad; Zhang, Zhiyong (Phytotaxa, 2023)
N/A